PENGEMBANGAN FILM ANIMASI 3 DIMENSI â€œTUDE THE MOVIE - PETUALANGAN SI RINA (HILANGNYA JALAK BALI DI ARENA MAKEPUNG)â€ - Rendy Syahrial, Lalu; Crisnapati, Padma Nyoman; Mahendra Darmawiguna, I Gede; Gede Sunarya, I Made (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2015)
The animated 3D movie entitled Tude the Movie - Rina's Exploration (the Lost of Jalak Bali in Makepung Field) is an animated movie which contains moral value that can be taken by the viewers, especially children. It is because this movie tells about how Tude and Pandu as the main characters teach us to be able to keep and care about our culture. The objectives of this study are: 1) Designing the animated 3D movie entitled Tude the Movie - Rinas's Exploration (the Lost pf Jalak Bali in Makepung Field) 2) Implementing the animated 3D movie entitled Tude the Movie - Rinas's Exploration (the Lost pf Jalak Bali in Makepung Field) In the process of making this animated 3D movie, the reasearch method or the research design used is Diagram Block.This Block Diagram explain about the steps of making the 3D animated movie entitled Tude the Movie - Rinas's Exploration (the Lost of Jalak Bali in Makepung Field) from the beginning until the ending. The stage of Diagram Block can be divided into 3 (three) steps, namely 1) Pre Production (The Story Idea, Script/ Synopsis Writing, Output Format Decision, Characters Design, Additional Pictures Design, and Storyboard Making), 2) Production (Modelling, Texturing, Ringging, Skining, Acting/Animation, Lighting, and Rendering), 3) Pasca Production (Shooting and Editing Process).The final product is in the form of animated 3D movie with DVD format. This movie is expected to give an interesting and educating movie to the viewers, especially children. Besides that, by the process of making this movie, the artists of Indonesia animated movie can be encouraged to produce the other animated movie which have better quality. Therefore, the animated movies are getting various in the local television and importing animated 3D movies from other countries is not needed anymore.